Analisis Pengaruh Keputusan Investasi Mahasiswa - Lilis Ayudiastuti (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
In Indonesia, the capital market experiences very rapid growth. The increase of the IDX Composite in 2016 was an indicator of capital market developments and affects investment activities. The investment activities related to the investment judgments of investors are affected by many factors. This study discusses the impact of financial literacy, herding behaviour, risk perception, overconfidence, experience regret, and the illusion of control on investment decisions. This study used 100 equity investors registered in an investment gallery at the Universitas Nusantara PGRI Kediri as samples. The analysis technique is SEM PLS. Results show that financial literacy, overconfidence, and illusion of control affect investment decisions. Besides, herding behaviour, risk perception, and experience regret do not influence investment decisions. The significance of these findings is to provide knowledge about the aspects and factors that influence investment decisions. Financial literacy allows investors to gain more information and learn about investments to avoid and prevent risks. Overconfidence gives investors sufficient certainty and information in making decisions by paying attention to the risks to prepare themselves to receive returns from the undertaken investments. The illusion of control makes investors believe in their abilities which can trigger investment results. Students with better financial knowledge can make better investment decisions.